NextBASS: a new low-frequency CMB foregrounds instrument - Hill-Valler, J (2019)
The Next Band All-Sky-Survey (NextBASS) is an instrument capable of measuring the diffuse Galactic Foregrounds continuously in frequency between 7 to 30 GHz, in both temperature and polarisation. Still currently in the design phase, NextBASS will obtain a resolution of ≤ 1◦, using a 6m cross-Dragone telescope with two bands, a single feed operating at 7 – 15 GHz and a 33-feed array of corrugated feed horns for 15 – 30 GHz. NextBASS will achieve a raw sensitivity of ≈ 9.4µKdeg for band-1, and ≈ 1.7µKdeg for in band-2. This sensitivity estimate is based on a conceptual 5 year survey, modelled with the atmospheric conditions and a visible sky fraction mirroring those of the Llano de Chajnantor Observatory. The receiver and digital back-end technologies will use continuous wave stabilisation with a low-bit and fast sampling ADC, and digitalsignal-processing performed in an FPGA. Using single pixel forecasting simulations with Bayesian parametric fitting methods, I demonstrate that NextBASS is capable of measuring a synchrotron spectral curvature term. Furthermore, NextBASS has the potential to detect the presence of a 1% polarised AME component, in regions of sky where the AME amplitude is bright comparative to other foregrounds. NextBASS will improve constraints on the diffuse foreground parameters and help remove bias on the cosmic microwave background B-mode amplitude. This thesis focuses on the motivations behind NextBASS by assessing its impact through single pixel forecasting, along with a full proof of concept, detailing the antenna and feed horn designs and developing a receiver model. The final performance of the combined optical and receiver system is capable of achieving beam efficiencies of over 96% in a 1◦ beam, yielding TSYS ≤ 34 K for all frequencies, and a cross-polarisation of less than -35 dB across the band.